Copy of letter from John Carstairs Matheson to James Connolly about unions and politics in the United Kingdom, the United States and France - Matheson, John Carstairs; Connolly, James, 1868-1916 (1909)
Matheson also refers to the "Damned Old Man", Industrial Workers of the World, [William Ernst] Trautmann, Advocates of Industrial Unionism and an "Allen".
Letter is addressed from "17 High Street / Lanark".
This is a typescript copy of MS 13,906/1/38.
Keywords: Matheson, John Carstairs -- Correspondence; Connolly, James, -- 1868-1916 -- Correspondence; Socialism; Great Britain -- Politics and government -- 1901-1910; United States -- Politics and government -- 1901-1909